Pelaksanaan Fungsi Pendamping Desa dalam Pengelolaan Dana Desa Tahun Anggaran 2020 di Desa Tebole dan Desa Lenguselu Kecamatan Rote Selatan Kabupaten Rote Ndao Berdasarkan Peraturan Menteri Desa Pembangunan Daerah Tertinggal dan Transmigrasi Nomor 3 Tahun - Andry Armando Dethan; Saryono Yohanes; Yosef Mario Monteiro (Pusat Riset dan Inovasi Nasional, 2024)
The development and progress of villages as the smallest units in the governance structure are crucial for sustainable national development. In this context, the role of village facilitators has a significant impact on assisting villages in realizing their full potential. Village facilitators play a crucial role in assisting village governments in effectively and efficiently managing village funds to achieve sustainable community development and empowerment. The research problems in this study can be formulated as follows: (1) To what extent is the implementation of facilitation functions by village facilitators in the management of village funds in the fiscal year 2020 in Tebole Village and Lenguselu Village, South Rote District, Rote Ndao Regency, based on the Minister of Village, Development of Disadvantaged Regions, and Transmigration Regulation Number 3 of 2015 Regarding Village Facilitation? And (2) What are the factors inhibiting the implementation of Village Facilitator functions in the management of Village Funds in South Rote District, Rote Ndao Regency? The purpose of this study is to describe the implementation of Village Facilitator functions in the management of Village funds in Tebole Village and Lenguselu Village. This study is a Juridical Empirical study where data is obtained directly from relevant parties or institutions. After collecting the necessary data, the researcher processes and categorizes the data according to its type and source. The population in this study is the Village Head, Village Facilitators, and the Community, totaling 13 people. The Village Head consists of 2 people, Village Facilitators consist of 1 person, and the Community consists of 10 people. The results of this study indicate that: (1) This study explores the implementation of village facilitator functions in the three main stages of village fund management: planning, implementation, and supervision of village development in Tebole Village and Lenguselu Village, South Rote District, Rote Ndao Regency. The results show that village facilitators have not effectively carried out their functions in these three stages. (2) Inhibiting factors in the implementation of village facilitator functions in the management of village funds in Tebole Village and Lenguselu Village. These factors include the low level of education of village facilitators, which reduces their effectiveness in assisting in the planning, implementation, and supervision processes, insufficient budget availability perceived by the village government and village facilitators, and a lack of support in infrastructure and facilities, which poses a serious obstacle for village facilitators. The author's recommendations for this study are that the government needs to improve the education and training of village facilitators, enhance budget transparency, strengthen partnerships with village governments, and provide adequate infrastructure and facilities to support the tasks of village facilitators. By implementing these recommendations, significant improvements in village fund management and local community progress are expected.